The Alma Mater Society Art Collection : University of British Columbia 1948-1988. (Vancouver : University of British Columbia, 1988)
Alleyn, Edmund ; Aspell, Peter ; Baxter, Ian ; N.E. Thing Co. ; Bobak, Molly ; Bolduc, David ; Breeze, Claude ; Brett, Leonard ; Burrows, Tom ; Burton, Dennis ; Chambers, John ; Curnoe, Greg ; Dickson, Jennifer ; Fafard, Joe ; Falk, Gathie ; Fisher, Brian ; Gilbert, Herb ; Harris, Lawren S. ; Henderson, D'arcy ; Hodgson, Tom ; Hughes, E.J. ; etc.
English
boek